Bean utilization and commercialization in great lakes region of Central Africa: the case of smallholder farmers in Burundi - Ochieng, J.; Ruraduma, Capitoline; Birachi, Eliud Abucheli; Wozemba, D.; Niyuhire, M.C.; Ouma, Emily A. (Pan-Africa Bean Research Alliance, 2010)
This paper evaluates production and commercialization constraints that prevent smallholder farmers from effectively utilizing beans with regard to household food and income security. The study was conducted in six provinces of Burundi in 2010 using a multi-stage stratified sampling procedure to select a sample of 380 smallholder bean farmers. Linear regression models were used to estimate factors influencing the quantity of beans marketed by smallholder farmers. Different ways in which beans are utilized include household consumption, selling, gifts and as seeds. Both improved and local seeds are used, with over 65% of farmers in Muyinga planting local varieties. Results showed that highly educated farmers were more likely to increase commercialization by 10%. However storage of beans for food was more likely to reduce commercialization by 23% while those who gave out beans as gifts had a higher (12%) chance of commercialization. Transport losses were likely to reduce commercialization by 15%, but knowledge of bean networks and access to information from traders was likely to increase bean commercialization by about 10%. Emphasis on interventions (information and extension services) that increase farm level productivity and market led approaches between potential buyers of beans and rural communities will help to reduce poverty and address food insecurity in rural areas.